The Relationship Between Endorsement of the Sexual Double Standard and Sexual Cognitions and Emotions - Emmerink, Peggy M. J. (Sex Roles, 2016)
Sexual gender norms promoting sexual prowess for men, but sexual modesty for women have been shown to negatively affect sexual and mental health in both men and women. Knowledge about the relationship between gender norms and sexual cognitions and emotions might further the understanding of continued gender-norm conformity. In the present study, we investigated whether and how gendered sexual attitudes are related to (positive and negative) sex-related emotions, via sexual cognitions (autonomy, body esteem, and approach/avoidance motives for sex). A survey was submitted to 293 heterosexually identified, sexually active, Dutch (central and southern regions) 18–25 year-olds. Results from a moderated mediation model (using structural equation modeling) revealed that women, but not men, who more strongly endorsed traditional gender-related sexual attitudes experienced significantly less positive and more negative emotions, as a result of decreased sexual autonomy and sexual body esteem as well as increased avoidance motives for sex. We conclude that, as a result of negative cognitions associated with the endorsement of traditional gender norms, women in particular are at risk of experiencing negative emotional outcomes in the sexual context. We argue that sexual cognitions and emotions deserve explicit attention in sex-positive and gender-transformative sexuality education, which has been proven to be a vital resource for achieving increased gender-equity in sexual and romantic relationships. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11199-016-0616-z) contains supplementary material, which is available to authorized users.